2022
DOI: 10.1093/narcan/zcac015
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genome-wide analysis reveals EIF3A as a key downstream regulator of translational repressor protein Musashi 2 (MSI2)

Abstract: Musashi 2 (MSI2) is an RNA binding protein (RBP) that regulates asymmetric cell division and cell fate decisions in normal and cancer stem cells. MSI2 appears to repress translation by binding to 3′ untranslated regions (3′UTRs) of mRNA, but the identity of functional targets remains unknown. Here, we used individual nucleotide resolution cross-linking and immunoprecipitation (iCLIP) to identify direct RNA binding partners of MSI2 and integrated these data with polysome profiling to obtain insights into MSI2 f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…To determine whether inhibition of MSI1/MSI2 by R12-8-44-3 would apply in a cellular context, we adapted an aptamer pull-down reporter assay that we previously used to validate candidate Musashi target genes [96]. Briefly, our approach is a variation of the MS2-TRAP (MS2-tagged RNA affinity purification) method, which uses bacteriophage protein MS2-BP to extract from cells any factors that associate with RNAs containing a specific stem-loop structure (MS2) from the phage genome [97].…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether inhibition of MSI1/MSI2 by R12-8-44-3 would apply in a cellular context, we adapted an aptamer pull-down reporter assay that we previously used to validate candidate Musashi target genes [96]. Briefly, our approach is a variation of the MS2-TRAP (MS2-tagged RNA affinity purification) method, which uses bacteriophage protein MS2-BP to extract from cells any factors that associate with RNAs containing a specific stem-loop structure (MS2) from the phage genome [97].…”
Section: Resultsmentioning
confidence: 99%
“…In flies and cultured mammalian cell lines the Musashi proteins repress translation of Numb and p21 Waf1/Cip1 , while in frog oocytes they activate early translation of Mos and Cyclin B5 after progesterone stimulation 21 , 26 , 53 , 54 . Furthermore, recent genome wide studies integrating ribosome profiling and RNA binding data showed that within the same cell MSI1 and MSI2 repress translation of certain transcripts while activating others 55 , 56 . The transcriptome-wide studies also show that translation of relatively few of the large numbers of transcripts that are bound by the Musashi proteins is affected when the levels of MSI1 and MSI2 are manipulated 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent genome wide studies integrating ribosome profiling and RNA binding data showed that within the same cell MSI1 and MSI2 repress translation of certain transcripts while activating others 55 , 56 . The transcriptome-wide studies also show that translation of relatively few of the large numbers of transcripts that are bound by the Musashi proteins is affected when the levels of MSI1 and MSI2 are manipulated 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequences of RRM1 and RRM2 of MSI1 exhibit 85% identity to those of MSI2 respectively, suggesting that the two proteins might target some mRNAs in a similar fashion. Indeed, an in vitro study identified the UAG RNA sequence as the core MSI1 binding motif [13], while recent genome-wide analyses of MSI2 targets revealed binding of MSI2 to mRNA 3'UTRs that contain multiple copies of UAG motifs as well as polyU pentamers [14,15]. Dysregulated expression of RBPs can be detected in various human diseases ranging from neurological disorders to cancer [16,17], rendering them potential targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%